Low Mortality and Key Aspects of Delivery of Care for End-Stage Renal Disease in Italy - Alexander Lauder; Arrigo Schieppati; Ferruccio Conte; Giuseppe Remuzzi; Daniel Batlle (The Scientific World Journal)
End-stage renal disease (ESRD) is a global health problem. There are differences in mortality among patients with ESRD amid industrialized countries that may be related to their respective systems of delivery of care. A nationwide survey was completed in Italy, a country with low mortality rate for ESRD patients, in order to help understand key aspects of ESRD delivery of care that contribute to mortality. Survey responses were obtained and analyzed from 131 of 575 dialysis centers (23%), covering data from 13,170 dialysis patients in 2006. The mortality rate was 11.2% and the prevalence of diabetes-associated kidney disease was 21%. Of the patients, 88% were on hemodialysis and 12% were on peritoneal dialysis. Most patients were in the age range of 65–75 years (66.7%), were seen by a nephrologist at CKD stage 3, and began dialysis at mean estimated GFR of 9.6 ml/min/1.73 m2. AV fistulae were the prevailing form of vascular access (83%) and were most frequently placed by a nephrologist (61.2%). In 98% of the dialysis centers, a nephrologist was present during dialysis sessions. The following may explain the low mortality for ESRD patients in Italy: low prevalence of diabetes, high use of AV fistulae, delivery of care by nephrologists beginning in pre-ESRD stages, their involvement in placement of dialysis vascular access, and their physical presence requirement during dialysis sessions. These findings portray key aspects of the contemporary delivery of care for Italian dialysis patients and provide a platform for international comparison of healthcare systems for ESRD.